Tidal Dynamics Control on Cold-Water Coral Growth: A High-Resolution Multivariable Study on Eastern Atlantic Cold-Water Coral Sites - Juva, Katriina; Flögel, Sascha; Karstensen, Johannes; Linke, Peter; Dullo, Wolf-Christian (Frontiers in Marine Science, 2020)
Cold-water coral (CWC) communities form complex benthic ecosystems in a distinct part of the water column. The exact processes supporting CWC reef growth and changes with time are still partly unsolved. Besides local hydrographic conditions, noticeable interactions of tidal flow with topography have been reported for CWC sites. Recent studies have suggested a tidally driven hydraulic control of flow over topographic features as a driver for local overturning at cold-water coral sites. This mechanism proposed a link between surface productivity and coral growth depths and is a driver of resuspension of the bottom material. Only few studies have concentrated on how these processes vary with the health status and structure of the cold-water coral occurrences. In this study, we explore the processes over tidal cycles by analyzing in situ stratification, hydrography and velocity data which we then combine with local topography from seven Desmophyllum pertusum (previously Lophelia pertusa) dominated eastern Atlantic CWC sites, from the Arctic to the southern hemisphere. The “quality” of CWC sites varies from thriving to declining and dead reefs. We show that living and healthy corals are concentrated at sites, where local hydrodynamics create overturning and mixing which overcomes on a daily basis gravitational particle sinking and thus re-supply food to filter-feeding corals. We find a very wide range of local hydrographic and biogeochemical conditions at the sites which suggests they play only a secondary role for CWC health.